Behavioral and socio-economic determinants of urban households’ investment in energy efficient technologies: evidence from Ethiopia - Hassen, Sied; Anandarajah, Gabrial; Seifemichael, Robel (Frontiers in Energy Research, 2023)
Wide uses of energy-efficient technologies have the potential to save a significant amount of electricity, which may allow deferral of construction of new power plants. However, in low-income countries, there is low use of energy-efficient technologies. This paper studies the behavioral and socio-economic determinants of urban households’ investment in energy efficiency improvements in Ethiopia. It considers multiple technologies and uses a multivariate probit model to take into account the sequential or simultaneous adoption of energy-efficient technologies. Using a random sample of 1,400 urban households from nine regions in Ethiopia, the study finds that most households (86%) adopt energy-efficient technologies and other energy conservation activities mainly to reduce energy expenditure. Interestingly, at least 12% of the respondents adopt these activities out of concern for the environment and future generations, which is encouraging. The multivariate probit regression result shows that households’ educational status, income or occupational status, access to credit, and age are significant determinants of households’ investment in energy-efficient technologies. The results illustrate there is a need for policies that incentivize or promote firms to sell energy-efficient products, for example, using installment (credit) and also a policy on the language of product specifications–using local language.